Testicular Structure and Seminal Pathway in the Yellowtail Tetra Astyanax altiparanae (Characiforms: Characidae) - de Siqueira-Silva, D. H.; Dos Santos-Silva, A. P. [UNESP]; Bashiyo-Silva, C. [UNESP]; Rodrigues, M. S. [UNESP]; Vicentini, C. A. [UNESP]; Ninhaus-Silveira, A. [UNESP]; Veríssimo-Silveira, R. [UNESP] (Wiley, 2017)
This study aimed to describe testicular and its main ducts structure in the yellowtail tetra Astyanax altiparanae, contributing to the knowledge of the region in which semen is produced, storage and released, focusing mainly on the dynamic of germinal epithelium and Sertoli cells during germ cell maturation. Ten sexually mature male A. altiparanae had their testes processed according to the routine protocols to optical microscopy. Moreover, spermatic ducts and tubular compartment of the testes of three specimens were perfused with vinyl resin for gross anatomy and scanning electron microscopy. Astyanax altiparanae testes are paired organs, separated for most of their extension, joining posteriorly in a spermatic duct formed by a squamous simple epithelium. Seminiferous compartment presents anastomosing tubular type organisation, and spermatogonia spread along its extent. Spermatogenesis is of cystic type, and there is no main testicular duct. Spermatogenesis develops in ‘waves’, from posterior to anterior part of the gonad. Thus, while sperm is storage posteriorly, spermatogenesis keeps maturing germ cells anteriorly, making the germinal epithelium very dynamic, holding Sertoli cells that change their function as a cystic envelope to produce secretions of the seminal fluid and store sperm. Such kind of development is thought to be responsible by the high prolificacy of this species.